Canadian medicare : we need it and we can keep it - Duckett, S. J. (MQUP, 2013)
Medicare has been a crucial part of Canadian identity for nearly fifty years, and it stands in marked contrast to the US health system. But these facts alone do not protect it from dismissive swipes and criticisms, claims that the system is unsustainable, and even proposals to change medicare's fundamentals. In Canadian Medicare, Stephen Duckett and Adrian Peetoom show that the shared values underpinning medicare still provide a sound basis for the system's design. While medicare remains an important pillar of Canadian policy, changes can and must be made. The authors argue for improved primary care to better address increases in chronic diseases, a comprehensive strategy to provide care for the elderly, and the introduction of pharmacare. They demonstrate how, with proper investment, the health of Canadians can be maintained and even enhanced while the nation remains financially responsible. Accessibly written and clearly presented, Canadian Medicare is a call for Canadian citizens to improve on the foundation built by Tommy Douglas and Lester B. Pearson, to become more knowledgeable about their health care, and to let their politicians know that they need to act.